2016
DOI: 10.1021/jacs.5b11390
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Explanation of the pH Dependence and Onset Potentials for Hydrocarbon Products from Electrochemical Reduction of CO on Cu (111)

Abstract: Energy and environmental concerns demand development of more efficient and selective electrodes for electrochemical reduction of CO2 to form fuels and chemicals. Since Cu is the only pure metal exhibiting reduction to form hydrocarbon chemicals, we focus here on the Cu (111) electrode. We present a methodology for density functional theory calculations to obtain accurate onset electrochemical potentials with explicit constant electrochemical potential and pH effects using implicit solvation. We predict the ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
457
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 436 publications
(490 citation statements)
references
References 23 publications
28
457
2
3
Order By: Relevance
“…In our previous work, 18 we showed that our GC-QM methodology leads to onset potentials within 0.06 eV of experiment for pH 1, 7, and 12, validating the accuracy of the level of DFT theory, the CANDLE solvation model, and the GC-QM method. In order to provide additional experimental tests of our very detailed mechanisms for subsequent product formation during CORR on Cu(111), we propose here several specific probe molecules that could be introduced to access new pathways at each pH while avoiding the constraint in CORR whereby pH selects C 1 or C 2 pathways.…”
Section: Journal Of the American Chemical Societysupporting
confidence: 72%
See 3 more Smart Citations
“…In our previous work, 18 we showed that our GC-QM methodology leads to onset potentials within 0.06 eV of experiment for pH 1, 7, and 12, validating the accuracy of the level of DFT theory, the CANDLE solvation model, and the GC-QM method. In order to provide additional experimental tests of our very detailed mechanisms for subsequent product formation during CORR on Cu(111), we propose here several specific probe molecules that could be introduced to access new pathways at each pH while avoiding the constraint in CORR whereby pH selects C 1 or C 2 pathways.…”
Section: Journal Of the American Chemical Societysupporting
confidence: 72%
“…18 We show here that the C 2 pathway leads to formation of HOCCOH ad via H 2 O ad (2d) just as for pH 13 but with a lower uphill pH dependent ΔG of 0.47 eV, which then blocks kinetically the branch to OCC ad formation (2e). Just as for pH 13, the C 2 pathway is followed by production of HOCC ad via H 2 O ad (2f).…”
Section: Journal Of the American Chemical Societymentioning
confidence: 65%
See 2 more Smart Citations
“…Indeed most quantum mechanics (QM) calculations have been performed with constant total number of electrons (constant charge), instead of the constant potential conditions of the experiments. The difficulty of QM for treating charged systems in solution has made such constant potential calculations a formidable task until the recent implementation of the constant potential DFT in conjunction with the CANDLE implicit solvent method by Sundararamen et al 8 and applied recently to CO 2 reduction at Cu surfaces 9 .…”
Section: Introductionmentioning
confidence: 99%